Long-term outcomes of cable-suspended suture technique versus conventional suture for anterior vaginal wall prolapse: a retrospective cohort study - Qian Hu; Shuai Huang; Xiaoke Yang; Ye Li; Qiubo Lv (BMC, 2023)
Abstract Background Anterior colporrhaphy (AC) is a conventional surgical repair technique for cystocele but with high recurrence rate. We present a novel technique: Cable-suspended structure (CSS) by non-absorbable suture combined with "bridge" formation in surgical treatment of cystocele. This study aimed to evaluate and compare the long-term outcome of CSS technique for anterior vaginal wall repair with AC. Methods A retrospective review was performed on patients who underwent anterior vaginal wall repair between January 2012 and March 2017 at our center. All the patients were under a follow-up survey. The primary outcomes were objective cure (anterior prolapse POP-Q ≤ stage 1) and subjective cure (no symptoms of bulge or retreatment for prolapse). Secondary outcomes included quality of life (QOL) and patients' satisfaction, outcomes of site-specific POP-Q points Aa, Ba and C, as well as postoperative complications. Results Of 91 included participants, 43 underwent AC and 48 underwent CSS. The proportion of sarcrospinous ligament fixation in the CSS group was higher than in the AC group (81.4% vs. 77.1%, P < 0.05). At a median follow-up of 69 months, the CSS group showed significantly higher objective cure rate compared with the AC group (72.9% vs. 51.2%, odds ratio 2.57, 95%CI 1.07-6.16). After adjusting for sarcrospinous ligament fixation, the CSS group still significantly showed higher objective cure rate (adjusted odds ratio 2.88, 95%CI 1.16-7.21). The proportion of the patients with POP-Q 0 stage in the CSS group was particularly higher than the AC group (25% vs. 7.0%, P = 0.025). There was no difference between the groups with respect to subjective cure, patients' satisfaction and postoperative complication. Conclusions The CSS technique showed better objective outcome than AC, however, subjective cure rate did not significantly differ between the two. Future prospective trial with large-scale should confirm the effectiveness and safety of CSS in sexually active women.